A Community Based Cross Sectional Study to Estimate the Prevalence and Associated Factors of Hypertension in Rural Nepal - Chataut, J.; Jonchhe, S.; Tamrakar, D. (Kathmandu University Medical Journal, 2020)
Background Hypertension is a major global public health problem because of its high prevalence as it significantly increases the risk of heart attack, stroke, kidney failure and blindness. Epidemiological shift in prevalence of non-communicable diseases have been observed in Nepal and it is also evident that hypertension and related complications are major contributors to death and disability in Nepal. Objective To estimate the prevalence and explore the associated factors of hypertension in study population. Method A community based cross-sectional study was conducted in rural population of Nepal with multistage sampling design. A total of 422 participants aged 18 to 65 years of age participated in the study. The information was obtained using pretested questionnaire which included demographic information of individuals and other risk factors like alcohol and tobacco use, physical activity. Anthropometric measurements and blood pressure was recorded and hypertension was defined as per JNC VII criteria. Result The overall prevalence of hypertension was 27.7% (male: 32.7%, female: 19.8%). Mean systolic and diastolic BP were 123.79 ± 12.46 mmHg and 81.56 ± 8.32 mmHg, respectively. Age (eldest age group, AOR=4.92: CI: 1.24-19.46), participants with lower level of education (higher education, AOR=0.173: CI: 0.05-0.53), ethnicity (Janajatis, AOR=2.85: CI: 1.44-5.65) and smoking (current smokers, AOR=10.30: CI: 4.39-24.16) are found to be significantly associated with hypertension. Conclusion This study showed the prevalence of hypertension is high in study population. Increasing age, low level of education, ethnicity and smoking were independent risk factors for hypertension.